2015
DOI: 10.17675/2305-6894-2015-4-3-269-283
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of biopolymers and synthetic polymers as hydroxyapatite dispersants for industrial water systems

Abstract: The dispersion of hydroxyapatite, Ca 5 (PO 4 ) 3 OH, HAP, by a variety of biopolymers and synthetic polymers of different composition and ionic charge has been investigated. The dispersion data show that polymer effectiveness as HAP dispersant strongly depends upon polymer architecture. Results also reveal that synthetic polymers perform better than biopolymers. It has been found that anionic, non-ionic, amphoteric, and cationic surfactants are ineffective as HAP dispersants. Additionally, it has also been obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The use of -COOH containing homopolymers such as poly(acrylic acid), PAA; poly(maleic acid), PMA; poly(aspartic acid), PAS; poly(itaconic acid) as scale inhibitors and dispersants for various scale forming salts and particulate matter has been well documented [20,21]. Results of these studies suggest that performance of these polymers depends on various factors including molecular weight (MW), polymerization solvent, and end group.…”
Section: Homopolymers Performancementioning
confidence: 99%
“…The use of -COOH containing homopolymers such as poly(acrylic acid), PAA; poly(maleic acid), PMA; poly(aspartic acid), PAS; poly(itaconic acid) as scale inhibitors and dispersants for various scale forming salts and particulate matter has been well documented [20,21]. Results of these studies suggest that performance of these polymers depends on various factors including molecular weight (MW), polymerization solvent, and end group.…”
Section: Homopolymers Performancementioning
confidence: 99%
“…The incompatible blending of formation water and salt water can significantly hinder increased oil recovery by causing the production of scales such as (CaCO 3 , CaSO 4 , BaSO 4 , SrSO 4 ) . At many production locations, a thick layer may develop, leading to problems like partial or whole duct blockages, which would result in a large rise in production costs. , The composition of ions in water and the degree of supersaturation with ions are the two main factors affecting salt precipitation. Furthermore, supersaturated water can contain various ions, resulting in the crystallization of several salts at the same time …”
Section: Introductionmentioning
confidence: 99%
“…Some studies have investigated celestite growth and precipitation rates at various experimental conditions without scale inhibitors. ,− Other studies also reported the effect of scale inhibitors on the precipitation rate of celestite under mild conditions (around room temperature, low ionic strength). , He et al (1995b) studied the t ind of celestite crystallization without and with two phosphonate inhibitors and one carboxylate inhibitor with the background of 1 M NaCl and T = 25–90 °C . However, no quantitative models were developed beyond these experimental results to evaluate the MIC needed for celestite scale control, making accurate celestite scale management hard to achieve.…”
Section: Introductionmentioning
confidence: 99%